JARINGAN SOSIAL ANTARA PENGRAJIN FURNITURE DENGAN DISTRIBUTOR BAHAN BAKU ROTAN DI KECAMATAN RUMBAI KOTA PEKANBARU - Reka Anggreini Putri; Mita Rosaliza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the social network between furniture craftsmen and distributors of rattan raw materials in Rumbai District, pekanbaru city. The design of this study is descriptive qualitative using observation techniques, in-depth interviews and documentation of informants. This research technique aims to determine the shape of social networks and the process of forming social networks among rattan craftsmen and distributors. The results of this study indicate that social networks are formed because in the background with honesty, good norms and trust between actors in them. Based on the results of this study, trust, honesty and good social norms greatly influence the establishment of a social network of furniture craftsmen with rattan distributors in Rumbai Pekanbaru District.Keywords: Social Networks, Furniture Craftsmen, Rattan Distributors